Innovative strategy for full-scale polar components explicition and ultrasonic-assisted optimization of Astragalus membranaceus flower - Yumei Wang; Meiling Gu; Meng Zhang; Jialin Mao; Yujian Han; Qi Liu (Ultrasonics Sonochemistry)
Traditional extraction under merely one specific solvent was confronted with incomplete phytochemical unscramble problem. In view of this, in order to obtain the overall chemical understanding, we attempted to use Astragalus membranaceus flower, an abundant exploitable resource, to screen a novel extraction mixing scheme via gradient solvents based on the ions’ quantity detected in UHPLC-Q-TOF-MS/MS approach. Samples were firstly extracted by different concentration ethanol, and then, six mixing schemes were investigated and one scheme with maximum detected ions was screened out. After identification procedures based on an comprehensive reference database, 136 components covered 54 flavonoids were accurately identified, indicating that flavonoids may played a critical role in Astragalus membranaceus flower. Through the Box–Behnken Design optimization, 29.79 mg/g of flavonoids were extracted under ethanol concentration of 35 %, solid–liquid ratio of 1:50, extraction time of 50 min. The experiments showed that the established mixing scheme could obtain more comprehensive ingredients compared to orthodox extraction, further guide the optimization of significative ingredients scientifically. The present paper could promote the development of Astragalus membranaceus flower.